Attraction of Culex mosquitoes to aldehydes from human emanations - Leal, Helena M.; Hwang, Justin K.; Tan, Kaiming; Leal, Walter S. (Scientific reports, 2017)
Anecdotes related to preferential mosquito bites are very common, but to date there is no complete explanation as to why one out of two people systematically receives more mosquito bites than the other when both are equally accessible. Here we tested the hypothesis that two constituents of skin emanations, 6-methyl-5-heptan-2-one (6-MHO) and geranylacetone (GA), are natural repellents and may account for differential attraction in different ratios. We studied skin emanations from two human subjects, confirmed in behavioral assays that female southern house mosquitoes are significantly more attracted to subject A (attractant) than to subject N (non-attractant), and tested their 6-MHO/GA ratios in a dual-choice olfactometer. Although repelling at high doses, 6-MHO/GA mixtures were not active at the levels emitted by human skin. We found, however, differential attraction elicited by the aldehydes in the ratios produced by subjects A and N. When tested in a dose commensurate with the level released from human skin and in the ratio produced by subject A, the aldehyde mixture significantly attracted mosquitoes. By contrast, an aldehyde mixture at the same ratio released by subject N did not attract mosquitoes. We, therefore, hypothesized that aldehydes may play a role in the commonly observed differential attraction.